The Protective Effect of Heparin in a Dog Model of Rethrombosis Following Pharmacologic Thrombolysis - Voytik, Sherry; Badylak, Stephen F; Burke, Sandra; Klabunde, Richard E; Henkin, Jack; Simmons, Abby (Thrombosis and Haemostasis, 1990)
Rethrombosis is an important clinical problem for patients who have benefitted from pharmacologic thrombolysis. The present study describes a dog model of arterial thrombosis, which includes endothelial denudation, intimal damage, and stenosis, and is suitable for studying the phenomena of both thrombolysis and subsequent rethrombosis. The model was used to determine the effect of tissue-type plasminogen activator (t-PA), high and low dose heparin, and saline upon the incidence of rethrombosis after t-PA-induced thrombolysis. Initial thrombolysis with reflow was achieved with 0.4 mg/kg t-PA, intravenous bolus injection, followed immediately by 0.4 mg/kg t-PA, 30 min infusion, in 40 of 42 dogs (95%) that had an occlusive, 125I-labelled thrombus created in a segment of femoral artery. The 40 dogs in which reperfusion was achieved were randomly sorted into 4 groups of 10 each which then received either saline, t-PA (0.4 mg kg−1 infused over 1 h), low dose heparin (500 U bolus injection then 250 U h−1 for 24 h), or high dose heparin (1,500 U bolus injection then 500 U h−1 for 24 h). Sixty percent (6/10) of the saline treated dogs showed occlusive rethrombosis at 24 h. The incidence of occlusive rethrombosis was 9/10 in the t-PA treated group (p = NS), 3/10 in the lowdose heparin treated group (p = NS), and 0/10 in the high dose heparin treated group (p <0.01). Two smaller groups consisting of 5 dogs each were treated with either saline or high dose heparinalone (no t-PA). None of the dogs in either group showed thrombolysis with reflow. All of the high dose heparin treated dogs and half of the low dose heparin treated dogs had prolonged values for the prothrombin time, activated partial thromboplastin time, and thrombintime through 24 h. All dogs treated with t-PA followed by additional t-PA had transient prolongations of the coagulation test values and also had a decrease in the plasma α2-antiplasmin concentration. These results suggest that heparin, when givenin high enough doses to cause risk of hemorrhage, provides protection against arterial rethrombosis following t-PA induced thrombolysis in a dog model of this clinically relevant problem.